Applying design thinking methods to ecosystem management tools: Creating the Great Lakes Aquatic Habitat Explorer. (July 2016) - Goodspeed, Robert; Riseng, Catherine; Wehrly, Kevin; Yin, Wenting; Mason, Lacey; Schoenfeldt, Benjamin
Abstract: Ecosystem management (EM) requires new tools to facilitate stakeholder access to information and analysis, however these tools are often not perceived by stakeholders to be usable, useful, and salient to their concerns. This paper provides a case study which applies new participatory design methods, known as design thinking, to create an EM tool called the Great Lakes Aquatic Habitat Explorer. Both participating and non-participating stakeholders rated the usability of the resulting tool positively, and stakeholders who attended design workshops rated the perceived usefulness and salience of the resulting tool more highly than those who had not. Design workshop survey data found that the methods produced an environment of collaborative learning among participants, including diverse participants, authentic dialog, and creativity. Design thinking methods hold promise for the development of new tools which better respond to the needs of EM stakeholders. Highlights: Design thinking methods were used to create an ecosystem management (EM) tool. The methods fostered creativity, engagement, and learning at design workshops. Participants rated tool usefulness and salience higher than non-participants. Creators of EM tools can result in improved outcomes through new design methods.